Pseudomonas aeruginosa LecB suppresses immune responses by inhibiting transendothelial migration. (1st March 2023) - Sponsel, Janina; Guo, Yubing; Hamzam, Lutfir; Lavanant, Alice C; Pérez‐Riverón, Annia; Partiot, Emma; Muller, Quentin; Rottura, Julien; Gaudin, Raphael; Hauck, Dirk; Titz, Alexander; Flacher, Vincent; et al.
Abstract: Pseudomonas aeruginosa is a Gram‐negative bacterium causing morbidity and mortality in immuno‐compromised humans. It produces a lectin, LecB, that is considered a major virulence factor, however, its impact on the immune system remains incompletely understood. Here we show that LecB binds to endothelial cells in human skin and mice and disrupts the transendothelial passage of leukocytes in vitro . It impairs the migration of dendritic cells into the paracortex of lymph nodes leading to a reduced antigen‐specific T cell response. Under the effect of the lectin, endothelial cells undergo profound cellular changes resulting in endocytosis and degradation of the junctional protein VE‐cadherin, formation of an actin rim, and arrested cell motility. This likely negatively impacts the capacity of endothelial cells to respond to extracellular stimuli and to generate the intercellular gaps for allowing leukocyte diapedesis. A LecB inhibitor can restore dendritic cell migration and T cell activation, underlining the importance of LecB antagonism to reactivate the immune response against P. aeruginosa infection. Synopsis: Pseudomonas aeruginosa lectin B binds to endothelial cells and inflicts junctional and cytoskeletal changes. Lectin B restricts migration of dendritic cells from tissue to lymph nodes and thereby has negative repercussion on adaptive immune responses. Pseudomonas aeruginosa lectin B binds to the lymphatics. Endothelial cells undergo cell structural changes upon LecB binding. Leukocyte diapedesis is inhibited by LecB. LecB inhibits T cell priming by impeding dendritic cell migration to the lymph node paracortex. Abstract : Pseudomonas aeruginosa lectin B binds to endothelial cells and inflicts junctional and cytoskeletal changes. Lectin B restricts migration of dendritic cells from tissue to lymph nodes and thereby has negative repercussion on adaptive immune responses.